Bibliometric Computational Mapping Analysis of Graphene-Based Surfaced – Enhanced Raman Scattering (SERS) During 2012 – 2022 - Afviva Nissa Vahendra; Asep Bayu Dani Nandiayanto (Universitas PGRI Semarang, 2022)
This study aims to examine the development of research related to Graphene-Based Surfaced-Enhanced Raman Scattering (SERS) through a bibliometric approach to computational mapping analysis using VOSviewer. The acquisition of article data was obtained from the Google Scholar database using the publish or perish reference manager application. The keywords used to guide the process of searching for the title and abstract of the article were